NUTRITION EDUCATION “FILL MY PLATE” FOR STUDENTS AT ELEMENTARY SCHOOL JATINANGOR, SUMEDANG, WEST JAVA - Bambang Aditya Nugraha Bambang Aditya Nugraha; Sulastini Sulastini; Sandra Pebrianti Sandra Pebrianti; Adelia F Fauzi Adelia F Fauzi; Alifa A Putri Alifa A Putri; Dervan S Rosadi Dervan S Rosadi; M T Bahtiar M T Bahtiar; Unais Zamzami Unais Zamzami; Nabila S Ramadani Nabila S Ramadani; Nathania A Trixie Nathania A Trixie; Najwa Sabrina Najwa Sabrina; Regatta A Dharma Regatta A Dharma; Tiara A Mazaya Tiara A Mazaya; Zahwa Z Lazuardy Zahwa Z Lazuardy (LP4M STIKes Karsa Husada Garut, 2024)
Elementary school students require adequate nutrition to supportlearning process, growth and development. Adequate nutritionallows students to have good academic achievement and avoidnutritional problems such as malnutrition and obesity. Therefore, anutritional education program for students entitled fill my plate wascarried out. This education contains a